The adoption of Facebook mobile application for managing learning - Lee, Cheng Ean Catherine *; Siew, Edwin Theng Fung * (2020)
Mobile technologies such as mobile device applications play a significant role within formal education and the use of social networking site such as Facebook through mobile devices has influence students’ management of learning in higher education. Researchers have identified a range of uses of Facebook mobile application in higher education. Despite the increasing use of Facebook mobile application by students and lecturers in higher education for educational purposes, very little empirical studies that concern the adoption of Facebook mobile application by university students in managing learning in the Malaysian higher education context. In this paper, we describe the likelihood of adoption of Facebook mobile application for managing learning by students of a private university in Malaysia, as well as how the perceived ease of use, perceived usefulness, and motivations of usage affect the behavioural intention of the students in adopting Facebook mobile application for managing learning. Through an online questionnaire survey, data were analysed using descriptive statistics, correlations and regressions. Results from the survey questionnaires (N=101) indicated a significant positive association between motivations of usage towards adoption of Facebook mobile application for managing learning as well as between perceived ease of use and perceived usefulness towards students’ adoption of Facebook mobile application for managing learning. In conclusion, students’ perceived ease of use, perceived usefulness, education purposes, information-seeking motive and interactivity were significant predictors of behavioural intention in adopting Facebook mobile application for managing learning.